PENGARUH LOKASI, BIAYA, DAN FASILITAS TERHADAP KEPUTUSAN BERSEKOLAH DI SMA TA TANGERANG - Ida Enestesa Nainggolan; Mohammad Bukhori; Rifki Hanif (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2026)
This study aims to analyze the influence of Location, Tuition Fees, and Facilities on students' enrollment decisions at SMA TA, Tangerang. The research is motivated by the intense competition among private schools in Tangerang, particularly in the Karawaci and surrounding areas. Therefore, understanding the factors that influence students' decisions is crucial for efforts to increase student enrollment and improve the quality of educational services. This study employs a quantitative approach with a survey method. The sample consists of 150 tenth-grade students at SMA TA, Tangerang for the 2025/2026 academic year, selected using a proportional random sampling technique. Data collection was conducted via questionnaires utilizing a Likert scale, and the data were subsequently analyzed using multiple linear regression. The results indicate that location, tuition fees, and facilities simultaneously exert a positive and significant influence on students' enrollment decisions at SMA TA, Tangerang. The coefficient of determination (R²) value of 0.552 demonstrates that 55.2% of the variance in the Enrollment Decision can be explained by the Location, Tuition Fees, and Facilities variables within the regression model, while the remaining variance is accounted for by other variables outside the scope of this study. The findings of this research are expected to contribute to academic development and serve as a reference for educational institutions to enhance their competitiveness and the quality of educational services provided to the community.